Ghrelin improves endothelial dysfunction through growth hormone-independent mechanisms in rats - Shimizu, Yoshito; Nagaya, Noritoshi; Teranishi, Yasuhiro; Imazu, Michinori; Yamamoto, Hideya; Shokawa, Tomoki; Kangawa, Kenji; Kohno, Nobuoki; Yoshizumi, Masao (Biochemical and biophysical research communications, 2003)
Ghrelin is a novel growth hormone (GH)-releasing peptide which was isolated from the stomach. We have reported that ghrelin causes vasorelaxation in rats through GH-independent mechanisms. We investigated whether ghrelin improves endothelial dysfunction. Ghrelin was subcutaneously administered to GH-deficient rats for three weeks. After isolation of the thoracic aorta, aortic ring tension was measured to evaluate vasorelaxation. Acetylcholine-induced vasorelaxation was impaired in GH-deficient rats given placebo compared to that in normal rats given placebo. GH-deficient rats treated with ghrelin, however, showed a significant increase in the maximal relaxation as compared with those given placebo. This improvement by ghrelin was inhibited by N G-nitro- l-arginine methyl ester, a nonselective nitric oxide synthase (NOS) inhibitor. Western blot analysis demonstrated that treatment with ghrelin increased endothelial NOS (eNOS) expression in the aorta of GH-deficient rats. These results suggest that administration of ghrelin improves endothelial dysfunction and increases eNOS expression in rats through GH-independent mechanisms.